SYN-THESIS AND INVESTIGATION OF FORMALDEHYDE, UREA POLYMERIC LIGAND BASED ON ANILINE (Scientific journal of the Fergana State University, 2023)
Objective: In the modern period of the development of science and technology, it is necessary to synthesize new types of sorbents, determine their complexing properties with respect to certain metal cations, study the composition, structure, and physicochemical properties of compounds formed in this process by extracting metal cations from a solution, the study of which is one of topical problems of inorganic chemistry. In this article, a new type of polymeric ligand based on urea-formaldehyde and aniline has been synthesized. The conditions for ligand synthesis, the effect of temperature on the polycondensation process, and the results of IR spectroscopic and thermal analysis of the sorbent were studied.